FAKTOR-FAKTOR YANG MEMENGARUHI POTENSI KECELAKAAN KERJA PADA PENGEMUDI TRUK DI PT BERKATNUGRAHA SINARLESTARI BELA WAN TAHUN 2015 - windy pranita; eka lestari mahyuni; umi salmah (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT The accident that happened to the company truck drivers besides harmed directly to the victims, also raised the big impact to the company. Therefore, a research about factors that influence to the potential of the work accident of the truck drivers at PT BerkatNugraha SinarLestari, Belawan in 2015. The research samples are 39 truck drivers. The characteristic of this research is analytic using cross sectional design. The data analysis used are univariate, bivariate using Exact Fisher test and multivariate using Binary Logistic Regression test with backward stepwise method. The result of the research shows that truck drivers who ever got work accident are 14 drivers (35.9%) and 25 drivers (64.1%) are never got work accident. The result of exact fisher test show that the condition of the vehicle, the condition of the road and the condition of the body physical have a corellation to the potential of the work accident. The result of binary logistic regression test with backward stepwise method show that the most significant variable influence is the condition of the body physical with value p=0,003 and Exp (/6)=0,065. According to the result of this research, it is suggested to PT BerkatNugraha SinarLestari to provide a seat bearing for truck driver in order to reduce the vibration when they go passing the broken road. After driving for 4 hours, the drivers must take a rest at least 30minutes. After that, drivers must stretch leg, hand, shoulder, and the whole body muscles in order to release muscle tension and drowsiness before continuing the trip. In addition, the truck drivers must provide mineral water during the trip in order to left out thirsty or drowsiness while driving and be careful when driving a truck.